Social services in the fulfillment of rights for poor family children in Bisa school, Bintaro, Tangerang Selatan - Uswandhian, Era Estu; Sokhivah, Sokhivah; Sahrul, Muhammad (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
BISA School is a non-formal educational institution under the auspices of the Hands for Others Foundation, which provides social services in a broad sense for children from low-income families in the Bintaro area, South Tangerang. This research aims to find out the programs and activities carried out by the BISA School in fulfilling children's rights. This study uses a descriptive qualitative approach. Data were obtained from primary and secondary data with data collection techniques by conducting interviews, observations, and documentation studies. Data analysis was carried out through data presentation, data reduction, and conclusion. The results of the study indicate that BISA School has several programs and activities that support the fulfillment of children's rights, including educational programs with teaching and learning activities for academic subjects..